2019
DOI: 10.14260/jemds/2019/757
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Regarding Caries Risk Assessment and Management in General Dentists- A Cross Sectional Survey

Abstract: BACKGROUND It is widely accepted that caries risk assessment (CRA) is the basis for management of dental caries in patients. The CRA can contribute to identifying people at high dental caries risk. The aim of this study was to assess the knowledge, attitude and practice of general dentists in the city of Kerman about CRA. METHODS The present descriptive cross-sectional study was conducted on 160 general dentists in the city of Kerman, Iran. Data collection tools consisted of demographic data and 10 questions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
2
Order By: Relevance
“…In the present study, majority (>70%) of the dental practitioners correctly identified caries as a multifactorial disease and several risk factors for caries ( Table 2 ) consistent with previous studies. 16 , 17 , 19 In addition, most participants correctly identified indicators of caries that include white lesions and interproximal lesions ( Table 2 ) in contrast to previous studies. 16 , 17 White lesions are the earliest visible changes on tooth due to caries and prompt application of preventive measures for these early lesions provides a very significant opportunity to stop caries progression to the stage at which surgical intervention is required.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In the present study, majority (>70%) of the dental practitioners correctly identified caries as a multifactorial disease and several risk factors for caries ( Table 2 ) consistent with previous studies. 16 , 17 , 19 In addition, most participants correctly identified indicators of caries that include white lesions and interproximal lesions ( Table 2 ) in contrast to previous studies. 16 , 17 White lesions are the earliest visible changes on tooth due to caries and prompt application of preventive measures for these early lesions provides a very significant opportunity to stop caries progression to the stage at which surgical intervention is required.…”
Section: Discussioncontrasting
confidence: 56%
“… 16 , 17 , 19 In addition, most participants correctly identified indicators of caries that include white lesions and interproximal lesions ( Table 2 ) in contrast to previous studies. 16 , 17 White lesions are the earliest visible changes on tooth due to caries and prompt application of preventive measures for these early lesions provides a very significant opportunity to stop caries progression to the stage at which surgical intervention is required. 7 Thus, the dental practitioners in Uganda need to be urged to offer preventive procedures and minimal invasive services aimed at remineralization of these early carious lesions.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Keeping track of each NCDT's strengths and limitations, while assessing their possible usefulness in daily dental practice and trying to reach an evidence based informed decision is especially is very important [15] yet challenging with busy clinicians' daily routines [32]. However, such difficulty does not seem to hinder the rising interest of dental practitioners in acquiring evidence-based intel regarding the newest caries detection and monitoring devices on the market [62,63]. This interest is noted in the current study, where most participating RDRs reporting their interest in NCDTs as a discussion topic.…”
Section: Main Indicationmentioning
confidence: 99%
“…As there is controversy among different available guidelines on risk-based management of caries and insu cient knowledge and practice regarding caries risk assessment and risk management (25), the purpose of the present study was to adapt an evidence-based CPG for risk-based caries management in 18-55 year-old Iranian adults.…”
Section: Introductionmentioning
confidence: 99%